Guidance on radiation received in space activities : recommendations of the National Council on Radiation Protection and Measurements. (NCRP report ;, 1989)
This report develops guidance on radiation exposures occurring in space activities. Radiation risk estimates for carcinogenesis, genetic effects and nonstochastic effects were utilized to develop risk comparisons on which career exposure limits are based. An important result of this approach is a differentiation in limits based on age and sex. Major sections of the report treat radiation environments in space, radiation exposure to personnel, radiobiological features of the space radiation environment, and radiation protection standards in space. The report also identifies needed research relevant to radiation exposures in space activities.